Self-Control and Crime/Deviance: Cognitive vs. Behavioral Measures - Tittle, Charles R. (Journal of quantitative criminology, 2003)
Using survey data, various measures of self-control, based respectively on cognitive and behavioral indicators, are compared in their ability to predict eight measures of crime/deviance. The results show that either type of measure produces supportive evidence for the theory, and the behavioral measures provide no better prediction than do the cognitive measures. Unlike cognitive type indicators, and contrary to the implications of the theory, different types of crime-analogous, imprudent behaviors are not highly interrelated, making it difficult to develop reliable behavioral measures. These results suggest that general support for self-control theory would likely not be any greater if all researchers had used behaviorally based measures, as recommended by the authors of the theory. Improving the level of prediction to the point where self-control could claim to be the master variable, as envisioned by its proponents, does not seem to rest on a shift to behaviorally based measures. Instead, improvements in the theory itself, particularly the incorporation of contingencies, appears to offer more promise.